E-Commerce Value-Added Tax Enforcement Strategies: A Comprehensive SWOT Analysis Approach - Destiny Wulandari; Antonius Ragil Kuncoro (Scientax: Jurnal Kajian Ilmiah Perpajakan Indonesia, 2026)
Tax enforcement is the single key factor that motivates tax compliance. It can enhance tax compliance because of the element of deterrence.  This study seeks to identify tax enforcement strategies that enhance E-Commerce Value-Added Tax (VAT) compliance in Indonesia. Conducting a qualitative methodology, the research explores document analysis, interviews, and focus group discussions with interviewees. A content analysis of the data was performed to identify Strengths, Weaknesses, Opportunities, and Threats (SWOT) to formulate tax enforcement strategies. The results of the study indicate that combining Strengths and Opportunities was the most appropriate strategy. The S-O strategies consist of: 1) integration of the registration system; 2) tax audit; 3) tax examination abroad; 4) service of document; 5) penalty imposition; 6) assistance in collection; and 7) access termination. The implications of implementing these strategies need collaboration with other parties and countries, using comparative data and international treaty instruments, and utilizing invoice data reported by taxable entrepreneurs. While numerous studies have discussed E-Commerce Value-Added Tax, this research is novel in its focus on tax enforcement strategies through a comprehensive SWOT analysis.